Energy storage at different voltage levels : technology, integration, and market aspects - Zobaa, Ahmed F.; Ribeiro, Paulo F.; Abdel Aleem, Shady H. E.; Afifi, Sara N. (IET energy engineering series ;, 2018)
The book consists of 12 chapters and discusses the following topics: overview of energy storage technologies; energy storage systems: technology, integration and market; energy storages in microgrids; energy storage in electricity markets; the role of storage in transmission investment deferral and management of future planning uncertainty; sizing of battery energy storage for end-user applications under time of use pricing; assessment and optimization of energy storage benefits in distribution networks; case studies from selected countries Romania and Italy; case studies from selected countries the USA; the use and role of flywheel energy storage systems; forecasting and optimisation for multi-purpose application of energy storage systems to deliver grid services: case study of the smarter network storage project; optimal coordination between generation and storage under uncertainties.